BIOACTIVE COMPOUNDS OF Moringa oleifera AS KRASG12C INHIBITORS IN COLORECTAL CANCER: IN SILICO STUDY - Marviella, Sephia Tiara; Zulqaida, Salma; Sulisetyawati, Theresia Indah Budhy; Ma'ruf, Anwar (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
KRAS is a GTPase enzyme that regulates cell growth and division. Mutations in KRAS can lead to its permanent activation, resulting in uncontrolled cell growth and cancer progression. Approximately 30–44% of colorectal cancer cases harbor KRAS mutations, with 1–3% involving the KRASG12C variant. Historically considered